The 'dead man walking' disorder: an update on Cotard's syndrome. (17th August 2020) - Tomasetti, Carmine; Valchera, Alessandro; Fornaro, Michele; Vellante, Federica; Orsolini, Laura; Carano, Alessandro; Ventriglio, Antonio; Di Giannantonio, Massimo; De Berardis, Domenico
Abstract: In 1880, Jules Cotard described a peculiar syndrome after observing the case of a 43-year-old woman, which was characterized by melancholic anxiety, delusions of damnation or possession, a higher propensity to suicide ideation and deliberate self-harm, analgesia, hypochondriac thoughts of non-existence or ruin of several organs, of the whole body, of the soul, of divinity, and the idea of immortality or inability to die. Several expansions and reinterpretations have been made of the so-called Cotard's syndrome, which is often encompassed in different neurological and psychiatric disorders, complicating and worsening their symptomatic frameworks and making more difficult their treatments. However, the nosographic characterization of Cotard's syndrome remains elusive and is not now classified as a separate disorder in both ICD and DSM-5. Here, we try to give an update, as well as a putative systematization, of current views and opinions about this nosological entity in the light of the recent progress in the clinic, psychopathology and psycho-neurobiology.